FEMINIZATION OF TEACHING - Rahayani, Yayan (Journal of English and Education (JEE), 2010)
We are turning a familiar fact into a feminization of teaching. How and why school teaching has shifted from a predominantly male to a female occupation, and why males handle the top managerial at school and leaves female keeps their position as classroom teacher. Feminization of teaching in one side provides opportunity for women to take part in public sphere, especially as the increasing demand of teacher for the compulsory program. On the other hand, it seems that feminization of teaching is merely seen as the extension of family matters, which are closely related to mothering and nurturing. Consequently, feminization projects another form of domestication for women. Sadly, this condition has been supported by the fact that women rarely get access to managerial position within the educational institution. This paper will discuss the feminization of teaching in general context.